Clinical ethics and patient advocacy: the power of communication in health care - Emrich, Inken; Fröhlich-Güzelsoy, Leyla; Bruns, Florian; Friedrich, Bernd; Frewer, Andreas (HEC Forum, 2014)
In recent years, the rights of patients have assumed a more pivotal role in international discussion. Stricter laws on the protection of patients place greater priority on the perspective and the status of patients. The purpose of this study is to emphasize ethical aspects in communication, the role of patient advocates as contacts for the concerns and suggestions of patients, and how many problems of ethics disappear when communication is highlighted. We reviewed 680 documented cases of consultation in a 10-year period of patient advocates' activity at a big German university hospital with 1,300 beds. On the basis of this extensive material, the article will focus on the intersection of the advocate's work with the problems of patients in hospitals. Deficits in the level of communication between health care professionals and patients were frequently uncovered. Patients primarily complain about the lack of dialogue and empathy. Middle-aged patients consulted the patients' advocate disproportionately more often. Measured against this baseline, the group of 65 and older complained less frequently. Besides complaints the advocate was asked in more than one-third of all cases for information about medical matters, hospital regulations or administrative problems. Patients obviously see the advocate as a well-connected and ideally unbiased contact person for uncertainties concerning their malady or a potential stay in hospital. Those seeking help often set hope in the information given by the voluntary patient representative. It should be highly recommended for every German hospital to establish the position of a patient advocate. Furthermore, patients can profit from regular exchange between the advocate and the Ethics Committee, also, to help ensure that their rights are taken into account and implemented in an ethically desirable context.
EVALuna2:5658